Determinates of Entrepreneurial Intention among Graduating Students of Bonga Polytechnic College, Kaffa Zone, Ethiopia - Abera Atto Ambo (International Journal of Entrepreneurship, Business, and Creative Economy, 2023)
The globe is currently experiencing a problem with unemployment, and entrepreneurship is the primary remedy to help economies recover from this crisis. Most TVET graduates are stressed by searching for salaried jobs rather than creating their businesses, which is against the mission of TVET. This motivated the researcher to study the factors determining the entrepreneurial intention of TVET students. The primary goal of this study was to identify factors that predict students at Bonga Polytechnic College to pursue entrepreneurial endeavors. The study used a quantitative technique and an explanatory research design. Primary data was collected through a survey questionnaire designed in the form of a Likert scale. Samples of 297 students were asked to complete a survey. The sample size was established using the stratified sampling technique. After the data had been collected, it was analyzed using inferential statistics such as correlation and regression with the help of SPSS v.24. The researcher found that student entrepreneurial intention was significantly influenced by gender, age, family background, attitude, entrepreneurship education, government policy, access to finance, physical infrastructure, commercial and legal infrastructure, and cultural and social norms. According to the findings of this study, each factor significantly influences entrepreneurial intention. The findings of this study contribute to the increasing body of literature on the factors that determine the entrepreneurial intentions of TVET students by providing practical contributions.